2014
DOI: 10.1007/s11274-014-1747-4
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenetic and genetic characterization of Acidithiobacillus strains isolated from different environments

Abstract: To study the phylogenetic relationships and genetic heterogeneity of 21 Acidithiobacillus strains isolated from different environments, we amplified and sequenced the 16S-23S rRNA gene intergenic spacers (ITS) of all these strains. These sequence data, combined with related sequences available from GenBank, were divided into six phylogenetic groups by 16S rRNA gene and by 16S-23S rRNA gene sequence analysis. The results of phylogenetic analysis were consistent with those obtained by repetitive element PCR and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 36 publications
1
1
0
Order By: Relevance
“…However, a number of additional lineages (phylotypes) with statistically well-supported nodes also became apparent in either, or in both, analyses, uncovering further inherent diversity for this taxon. This is in agreement with evidence derived from phylogenetic studies encompassing more restricted sets of strains, mostly focused on iron-oxidizing strains of the group (Amouric et al, 2011; Wu et al, 2014 and references therein), which have resulted in recent reclassification of a number of strains of A. ferrooxidans into the new species referred to above. In this work a total of 6 new phylotypes (16S rRNA clades 1B, 1C, 1D, 2B, 3A, 4B, Supplementary Table 4) were identified that are readily distinguishable by phylogenetic clustering and important levels of sequence divergence.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…However, a number of additional lineages (phylotypes) with statistically well-supported nodes also became apparent in either, or in both, analyses, uncovering further inherent diversity for this taxon. This is in agreement with evidence derived from phylogenetic studies encompassing more restricted sets of strains, mostly focused on iron-oxidizing strains of the group (Amouric et al, 2011; Wu et al, 2014 and references therein), which have resulted in recent reclassification of a number of strains of A. ferrooxidans into the new species referred to above. In this work a total of 6 new phylotypes (16S rRNA clades 1B, 1C, 1D, 2B, 3A, 4B, Supplementary Table 4) were identified that are readily distinguishable by phylogenetic clustering and important levels of sequence divergence.…”
Section: Discussionsupporting
confidence: 88%
“…However, in the last two decades, a variety of molecular tools suited for typing and identification of bacteria have been applied to further revise the taxon (reviewed in Nuñez et al, 2016). Acidithiobacillus strains of diverse origins have since been assigned to distinct phylogenetic subgroups and/or genomovars, thought to represent a number of unidentified cryptic species (e.g., Luo et al, 2009; Amouric et al, 2011; Wu et al, 2014). Based on a careful re-evaluation of phenotypic characteristics (e.g., capacity to oxidize molecular hydrogen, temperature, and pH tolerance profiles, tolerance to elevated concentrations of transition metals and chloride, presence of flagella, etc.)…”
Section: Introductionmentioning
confidence: 99%